Oxford handbook of U.S. social policy - BÃÂ¢eland, Daniel; Morgan, Kimberly J., 1970-; Howard, Christopher, 1961- (Oxford University Press, 2014)
This handbook provides a survey of the American welfare state. It offers an historical overview of U.S. social policy from the colonial era to the present, a discussion of available theoretical perspectives on it, an analysis of social programmes, and on overview of the U.S. welfare state's consequences for poverty, inequality, and citizenship.